Sensors in the Age of the Internet of Things: Technologies and applications - Postolache, Octavian Adrian; Sazonov, Edward; Mukhopadhyay, Subbas Chandra (Control, robotics and sensors series, 2019)
The IoT is the inter-networking of connected and smart devices, buildings, vehicles and other items which are embedded with electronics, software, sensors, actuators, and network connectivity that enable these objects to collect and exchange data. A sensor is a detection device that measures, records, or responds to a physical property. Sensors represent the front end of information processing. Progress in communication technologies is part of the multi-factorial advances in electronics, sensors, embedded computing, signal processing and machine learning methods that has led to the development of new capabilities in the IoT. This edited book focuses on the technologies constituting the IoT from a sensor perspective, for an audience of researchers, scientists, engineers and graduate students with an interest in the field. Applications covered include connected sensors for smart cities, energy infrastructure, emergency management, and smart ports.